Sensory evaluation techniques - Meilgaard, Morten C.; Civille, Gail Vance; Carr, B. Thomas (CRC Press, Taylor & Francis Group, CRC Press is an imprint of the Taylor & Francis Group, an Informa business, 2016)
"This new edition of a bestseller covers all phases of performing sensory evaluation studies, from listing the steps involved in a sensory evaluation project to presenting advanced statistical methods. Like its predecessors, Sensory Evaluation Techniques, Fifth Edition gives a clear and concise presentation of practical solutions, accepted methods, standard practices, and some advanced techniques. The fifth edition is comprehensively reorganized, revised, and updated. Key highlights of this book include:A more intuitive organizationStatistical methods adapted to suit a more basic consumer methodologyRearranged material to reflect advances in Internet testingNew time-intensity testing methodsNew chapters on advanced sensory processes, quality control testing, advertising claims, and business challengesNew material on mapping and sorting, graph theory, multidimensional scaling, and flash profiling techniquesExplanations of theories of integrity, amplitude, and balance and blendUpdated appendices for spectrum method scalesUpdated referencesSensory Evaluation Techniques remains a relevant and flexible resource, providing how-to information for a wide variety of users in industry, government, and academia who need the most current information to conduct effective sensory evaluation and interpretations of results. It also supplies students with the necessary theoretical background in sensory evaluation methods, applications, and implementations."--Provided by publisher.
Earlier editon: Sensory evaluation techniques / authors, Morten Meilgaard, Gail Vance Civille, B. Thomas Carr.
Keywords: Sensory evaluation.; Senses and sensation.; Food preferences.; elektronické knihy; electronic books